DESIGNING HUMAN CAPITAL MANAGEMENT SYSTEM IN PT. HARIFF POWER SERVICES (The Indonesian Journal of Business Administration, 2021)
PT. Hariff Power Services is national private company engaged in Mechanical and Electrical Services, especially transformer maintenance services. At the end of 2020, target for transformers quantity that must be repaired could not be achieved, causing company's revenue to not match the target, also some employees are dissatisfied with the company's current performance. Main factors that cause employee dissatisfaction are caused by ineffective work coordination, unclear details of work and miscommunication between individuals. This research aims to determine the implementation of several human resource management practices elements in an integrated human resource management system, so it can help company problems within scope of human resource management. This study uses 5 elements in human resource management practice, such as job analysis, performance measurement, competence, career management, and recruitment.Based on research results, it can be seen that more targeted job descriptions and job specifications have been prepared for each position as part of the job analysis, besides that more measurable Key Performance Indicator (KPI) framework has been developed for each position as part of performance measurement. In competency element, competency model that consist of 22 competencies dimension has been compiled for each position accompanied by competency level, where this competency level becomes data that will be processed using hierarchical cluster analysis to describe career-path for each position which is divided into 3 clusters and 3 job levels. In recruitment element, more integrated recruitment flow has been proposed along with determination of stakeholders and materials for each position.Keywords: human capital management practices, job analysis, performance measurement, competencies, career management, recruitment, mechanical electrical services, transformer